The Pricing of Durable Exhaustible Resources: Comment - Chilton, John (Quarterly Journal of Economics, 1984)
Journal Article The Pricing of Durable Exhaustible Resources: Comment Get access John Chilton John Chilton University of South Carolina Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 99, Issue 3, August 1984, Pages 629–637, https://doi.org/10.2307/1885968 Published: 01 August 1984